Peptidoglycan fragments decrease food intake and body weight gain in rats. - Biberstine, K J (1994)
We hypothesized that peptidoglycan (PG) fragments decrease appetite in rats. Male Lewis rats (150 g; n > or = 7) received intraperitoneal (i.p.) injections of purified soluble PG fragments that had been treated with polymyxin B-agarose to remove residual endotoxin. Food consumption and body weight gain were determined at intervals after injection. Single i.p. injections of macromolecular extensively O-acetylated PG (S-O-PG) and non-O-acetylated PG fragments (24 to 240 micrograms/kg) reduced food intake and body weight gain in a dose-dependent fashion during the first 12 h after injection. Low-molecular-weight disaccharide peptide monomers with nonreducing 1,6-anhydro-N-acetylmuramic acid ends and muramyl dipeptide (MDP; 1.6 mg/kg) were also appetite and weight gain suppressants, albeit at least 10-fold less potent than S-O-PG; however, muramidase-derived monomers and peptide cross-linked dimers with reducing muramic acid ends were inactive. Appetite suppression was not limited to the Lewis rat strain since another strain, F344, exhibited similar decreases in food intake after injection of S-O-PG or MDP. Oral administration of MDP or S-O-PG, at concentrations 3 and 20 times higher, respectively, than those that were active i.p., failed to elicit a hypophagic response. We conclude that soluble PG fragments are potent suppressants of food consumption and body weight gain in rats and that, although macromolecular PG is more potent than low-molecular-weight fragments, neither O-acetylation nor glycosidic linkage of PG fragments is required for activity. We speculate that PG fragments may contribute to loss of appetite during bacterial illness.